A TERRA ONDE CONSTRUÍMOS NOSSAS COMUNIDADES - Moreira, Silvana dos Santos (2015)
“The land where we build our communities” is a study based on the assumption that the occupation and use of land differ according to the historical origins of a specific community. The main objective of this study is to identify the characteristics of occupation and use of land in the community of Arroio Grande, located in the municipality of Irati, in the southern Brazilian state of Paraná, and their correlations with community organization. The community of Arroio Grande was selected for this study because its inhabitants are predominately peasants, who were organized in a faxinal, a collective system of land use and living, until 1980. Arroio Grande was also selected because today it is a community with various forms of land use, including one group of families that is opting for ecologically-based agricultural production. Since occupation of the lands in this community more than one hundred years ago, its soils have been used as a source of income for families, from forestry, agriculture and livestock production, all of which have eroded soil quality. This is an exploratory, qualitative study, the data for which was gathered using participant observation, a questionnaire and interviews. A preliminary bibliographic study was necessary to understand the historical occupation and use of land in Brazil, Paraná and the municipality of Irati, as well as the problem of soil degradation, which compromises the quality of life of entire populations. The research resulted in involvement of the researcher with families in the community, which enabled a very amicable interaction. The occupation of land in Brazil has been very unequal, and, from the beginning of its colonization to the present, land use has predominately been geared towards production of crops for export. Thus, peasant communities have not been prioritized in patterns of land occupation and use, including in the implementation of public policies in different spheres of power. Yet peasant communities persist, despite the advance of capitalism, a model that excludes them, into the countryside. The contrast between production of commodities and peasant agriculture is mainly in differing objectives of use. For rural capitalists, the land is merely a resource to maximize profits. Yet for peasant communities, land is the basis of their existence and the security of their livelihoods. This contrast is perceived in the landscape that shapes the two organizational models of agriculture in Brazil. Large farms invest in monocultures of commodity crops with the best prices on international stock exchanges, while peasant families produce a diversity of foods distributed by institutional marketing programs such as the federal Food Acquisition Program, farmers' markets and local businesses. The results of this research are the historical survey of the community of Arroio Grande, including its interrelations with the economic cycles of yerba mate and wood; understanding of diversified land use, where over 40% of the landscape has native forest cover; and the problems small farms in the community face due to division of land by inheritance, in which property size decreases for each generation, leading young people and adults to seek wage labor while maintaining residence in the community. The community’s characteristics of solidarity, reciprocity, cooperation and religiosity are very strong, which strengthen the ties of community life. Urban interactions reinforce the need for other forms of community organization, leading families to found associations, participate in municipal and state councils, and participate in Irati political life.